Problematique de gestion de l'elephant et perspectives des forets d'Afrique centrale - wa Won (Pachyderm)
Outlines the problems associated with the economic needs of the people in the regions which relate to habitat loss, land use conflict and wildlife utilization and effect elephant population management in the region.